(untitled) (Journal of Medicine, 2019)
Crying with bloody tear, called haemolacria is a very rare condition in medical practice. There are many conditions such as idiopathic thrombocytopenic purpura, trauma (accidental or induced), factors deficiencies, infections (Epstein Barr virus or bacterial), tumours (malignant melanoma or haemangioma), conjunctival telangiectasia, Rendu-Oslar-Weber disease related to haemolacria. But idiopathic haemolacria may occur in some cases. In our case report, a 17-year-old girl presented with idiopathic bilateral haemolacria and gum bleeding associated with pseudoseizure and psychogenic hyperventilation who was treated and well responded to adequate counselling and Amitriptyline. J MEDICINE JUL 2019; 20 (2) : 106-108